HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KEJADIAN BALITA STUNTING DI SATU KELURAHAN DI TANGERANG - Megalea Rut Harikatang; Mei Melysa Mardiyono; Meisa Karisma Br Babo; Lia Kartika; Prisca Adipertiwi Tahapary (Jurnal Ilmiah Keperawatan, 2020)
Background: Stunting is a condition where the lack of fulfillment of nutrition in children and is chronic. The incidence of stunting in Indonesia reached 30.8%. One factor related to stunting is the mother's knowledge. During interviews in the Binong and surrounding areas, it was found that ten mothers did not yet know about the meaning of stunting, two of whom had heard but did not know about stunting and eight of whom had never heard of stunting. Research Objectives: This study was conducted to determine the relationship of knowledge and attitudes of mothers with the incidence of stunting toddlers in Binong and surrounding areas. Research Methods: This study uses a quantitative method of correlational type. The population in this study are mothers who have toddlers in the Binong and surrounding areas. The sampling technique used in this study is a total sampling. The research instrument used a questionnaire. The data analysis technique used is a bivariate analysis using the chi-square test. Results: Bivariate test results with chi-square stated there was no relationship between maternal knowledge with the incidence of stunting (p = 1,000) and maternal attitudes with the incidence of stunting (p = 0.786). Recommendation: Nurses have the responsibility to give a comprehensive education with various media to enhance mother knowledge about stunting. Further research is needed to add different variables of perception, behaviour and parenting.